Offshoring within South African manufacturing firms: An analysis of the labour market effects. (23rd March 2022) - Pretorius, Anmar; Bezuidenhout, Carli; Matthee, Marianne; Blaauw, Derick
Abstract: South Africa's manufacturing sector experiences declining growth and labour demand, and increased imports of intermediate goods. The paper investigates the influence of offshoring on employment and wages for capital‐ and labour‐intensive industries and skilled and unskilled workers, using firm‐ and employer–employee‐level data. Unlike findings in developed countries, offshoring generally lowers employment in manufacturing firms and increases and decreases the percentage of unskilled workers and lower skilled workers, respectively. Increased narrow offshoring seemingly grows the cohort of unskilled workers, particularly in ultra‐labour‐intensive industries. As offshoring gains momentum, worker‐level earnings increase in capital‐ and labour‐intensive industries but decrease in ultra‐labour‐intensive industries.